Y Chromosome Microsatellites Variation in Bali Cattle (Bos sondaicus) Population - Winaya, A; Muladno, Muladno; Gurnadi, RE; Saefuddin, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
Seven Y chromosome specific microsatellites were typed in a sample of 36 unrelated males from Bali cattle breed. Analysis variation of microsatellites marker in Bali cattle were determinate from PCR products by using 7 primer pairs that flanking microsatellites (INRA008, INRA057, INRA062, INRA124, INRA126, DYS 199, and INRA 189). PCR products were separated by 10% polyacrylamide gel electrophoresis (PAGE), and silver staining method was used to detect allele polymorphism at each locus. From two different geographical breed origin showed that Bali cattle from Bali island has higher heterozygous (h=0.33) level than Lombok island (h=0.30), but the number of allele was few (only two alleles) in all of locus. It is indicated that Bali cattle from two geographical origins were not significant in genetic variation. We know that Y chromosomal microsatellite in general has tend to specific allele in breed comparing to autosomal chromosome, because allele come from only male or Y sex chromosome and it contrary to autosomal chromosome where allele is contributed from male and female. FAO has specified that minimum four distinct alleles per locus for proficient judgment of genetic differences between breeds and this study we only used one breed, so it may not significantly to discriminate in Bali cattle population. For next study we need more Y chromosomal microsatellite marker to discriminate more Indonesian breeds related to tracing the genetic potential and because males animal has roles in genetic spreading which can have an enormous impact on highly selected domestic animal populations. (Animal Production 11(3): 149-154 (2009) Key Words : Bali cattle , Y chromosome, microsatellite, allele